Association Between Antibiotic Treatment of Leptospirosis Infections and Reduced Risk of Dementia: A Nationwide, Cohort Study in Taiwan - Chao, Pei-Chun; Chien, Wu-Chien; Chung, Chi-Hsiang; Huang, Chih-Kang; Li, Hao-Ming; Tzeng, Nian-Sheng (Frontiers in Aging Neuroscience, 2022)
Background To explore the association between leptospirosis, the risk of dementia, and the potential protective role of antibiotic treatment. Methods We conducted a retrospective cohort nationwide, population-based study, from Taiwan’s National Health Insurance Research Database (NHIRD). We enrolled 1,428 subjects aged 50 years or above, in the index year of 2000, which included those retrieved from the NHIRD record. Dementia diagnosis and incidence over 16 years follow-up was retrieved from the NHIRD records. The Fine and Gray survival analysis was used to determine the risk of dementia, and the results were presented as a sub-distribution hazard ratio (SHR) with a 95% confidence interval. Results In the study period, 43 of the 357 leptospirosis patients developed dementia, as compared to 103 of the control group (930.90 vs. 732.49 per 105 person-years). By the Fine and Gray survival analysis, the leptospirosis was associated with the risk of dementia, and the adjusted SHR was 1.357 (95% confidence interval [CI]: 1.213–1.519, P < 0.001), across 16-year of the follow-up period. To exclude the protopathic bias, the sensitivity analysis was conducted. This analysis revealed that the leptospirosis was associated with the increased risk of dementia, even after excluding the dementia diagnosis within the first year (adjusted SHR = 1.246, 95%CI: 1.114–1.395, P < 0.001) or within the first 5 years (adjusted SHR = 1.079, 95%CI: 1.023–1.152, P = 0.028), antibiotic treatment for leptospirosis was associated with the reduced risk of dementia (P = 0.001). Conclusion Leptospirosis was associated with an increased risk for dementia, and antibiotic treatment was associated with a reduced risk. Further research will be necessary to explore the underlying mechanisms of this association.